Evaluation of Agonal Cardiac Function for Sudden Cardiac Death in Forensic Medicine with Postmortem Brain Natriuretic Peptide (BNP) and NT‐proBNP: A Meta‐analysis. Issue 3 (18th November 2019) - Cao, Zhipeng; Zhao, Mengyang; Xu, Chengyang; Zhang, Tianyi; Jia, Yuqing; Wang, Tianqi; Zhu, Baoli
Abstract: Sudden cardiac death (SCD) is an unexpected death caused by a sudden loss of cardiac function, which is currently a global public health problem. Evaluation of the agonal cardiac function of the deceased is a quite important task for the diagnosis of SCD in forensic medicine. Brain natriuretic peptide (BNP) and N‐terminal proBNP (NT‐proBNP) are currently considered as significant biomarkers for the diagnosis of heart failure in both clinical and forensic practices. To investigate the postmortem evaluation roles of postmortem BNP and NT‐proBNP levels for SCD, the present study meta‐analyzed eight related studies from Embase, Cochrane Library, PubMed, China Biomedical Literature Database, China National Knowledge Infrastructure, and Wanfang Data. Newcastle–Ottawa Quality Assessment Scale was used to assess the quality of the included literature, and the meta‐analysis was performed by RevMan 5.3.5 software. Postmortem NT‐proBNP in pericardial fluid showed higher levels in the SCD group than that of the non‐SCD group with the weighted mean difference = 3665.74, 95% confidence interval: 1812.89–5518.59, and p  = 0.0001. However, postmortem levels of BNP in pericardial fluid and NT‐proBNP in serum revealed no statistical difference between SCD and non‐SCD subjects. The results of present meta‐analysis demonstrated that postmortem NT‐proBNP in the pericardial fluid could be used as an ancillary indicator for evaluation of agonal cardiac function in forensic medicine.